Isolation of fuxoxanthin and fatty analysis from Padina australis and cytotoxicity effect of fucoxanthin of human lung cancer (H1299) cell lines - Noviendri, Dedi; Jaswir, Irwandi; Mohd. Salleh, Hamzah; Taher, Muhammad; Miyashita, Kazuo (2011)
Fucoxanthin has been successfully isolated from species of Malaysian brown seaweed, namely P. australis. The purity of the fucoxanthin is >98% as indicated by High Performance Liquid Chromatography analysis. This seaweed also contained a considerable amount of unsaturated fatty acids. There are thirteen fatty acids were detected with Gas Chromatography. However, in terms of fatty acid methyl ester (FAMEs) of eicosapentanoic acid (C20:5n-3), arachidonic acid (C20:4n-6), linoleic acid (C18:2n-6) and alpha-linolenic acid (C18:3n-3) contents from P.australis was found (2.06, 9.50, 6.37, and 2.83 %, respectively). For saturated fatty acids, palmitic acid (C16:0) was found to be the major fatty acid about 23.97%. Furthermore, data obtained from the MTT assay indicated that fucoxanthin reduced the viability of H1299 cell lines, showing an IC50 value was 2.45 mM.